Functions of the VAT, actual problems of administration - N. Z. Zotikov (Вестник университета)
Value added tax (hereinafter – VAT), like other taxes, has certain functions, among which regulatory, incentive, fiscal functions are distinguished. Being an indirect tax assigned to one budget, VAT occupies a significant place in the tax revenues of the federal budget. The degree of performance of certain functions, including fiscal, depends on the level of tax administration of this tax. At the same time, the functions performed by the tax are closely interconnected: strengthening the stimulating function of the tax weakens the fiscal function and vice versa. The relevance of the research topic is due to the importance of VAT in the country’s budget system. The article analyzes the dynamics of tax revenues in general, including VAT, in comparison with the dynamics of Gross domestic product (GDP). the methods used in tax administration, including those not provided for by tax legislation are investigated. Taking into account world experience, measures are proposed to improve the tax calculation mechanism. The purpose of the study is to examine the impact of tax functions, tax administration on budget revenues.